HARMONIC PROPORTIONS OF CHLOROPLAST NUMBER IN STOMATA OF GUARD CELL POPULATIONS IN SUGAR BEET (BETA VULGARIS L.) - S. I. Maletskii; S. S. Yudanova; E. I. Maletskaya (Вавиловский журнал генетики и селекции)
The variability of chloroplast number and plastotype number in stomata guard cell populations was analyzed. Experiments were done with three types of plants: inbreed lines, a synthetic population and commercial heterosis hybrids. Chloroplast numbers in stomata guard cells of different plant groups are different: the greatest chloroplast number was recorded in inbred lines and triploid hybrid, and the smallest, in commercial  hybrids. The greatest number of plastotypes was observed in inbreed lines, and the smallest, in hybrids. The fractal dimension of stomata guard cell populations was used for characterization of tissue cells in sugar beet. It estimates in a logarithmic scale the ratio between the chloroplast number and plastotype number. In the samples studied, it varied from 1,17 to 1,23 in inbred lines and from 1,23 to 1,35 in commercial hybrids (average 1,272).